Weaker Forms of Commuting Mappings in Metric and Menger Probabilistic Metric Space - Shah, Dilip Kumar; Bhatta, Chet Raj; Chaudhary, Ajay Kumar (Journal of Institute of Science and Technology, 2025)
This paper aims to discuss the update of the comparative study of non-commuting mappings in metric space and probabilistic metric space. This interrelationship study in weaker commuting maps helps researchers understand, analyze, and reach their research goal.